MEMBANGUN KEUNGGULAN RITEL MODERN MELALUI STRATEGI HARGA - CYNTHIA MT, . (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Modern Retail is basically a bargain which has a modern concept, and has a modern versatile system ranging from payments to be made directly or through cards such as credit cards and debut. As the development of the modern era, the modern retailing has exploded with modern retail establishment that elevates the prestige of someone in the buying and selling action, namely the presence of malls and shopping centers that can lift a person's prestige. The results of the discussion can be made several conclusions, among others: (1) Modern Retail is a retail managed with modern management, generally found in urban, as providers of goods and services with quality and good service to consumers who are generally members of the middle class and above. Among other modern retail malls, supermarkets, department stores, mini supermarkets, department stores, etc., (2) Consumers have a perception about the price, the higher the price of a product the higher the quality of the product, because consumers do not have a clue other than quality products in addition to price, and (3) Price help buyers to decide how to obtain the expected benefits based on the highest purchasing power and with the pricing of a product such as a discount and others. Keywords: modern retail, pricing strategy